Development and performance evaluation of large-scale auxetic protective systems for localised impulsive loads. Issue 3 (September 2019) - Remennikov, Alex; Kalubadanage, Dulara; Ngo, Tuan; Mendis, Priyan; Alici, Gursel; Whittaker, Andrew
Cellular core structures with a negative Poisson's ratio, also known as auxetic core structures, are gaining attention due to their unique performance in sandwich panel systems for protecting critical infrastructures and military vehicles that are at high risk of blast and impact loads due to accidental and deliberate events. To help develop a high-performance protective system, this article outlines the performance evaluation of five different auxetic cell configurations based on a quantitative/qualitative review of an experimental load–deformation relationship of three-dimensional-printed auxetic panels from nylon plastics and the overall performance evaluation of metallic re-entrant honeycomb core sandwich panels as one type of lightweight protective system under static and dynamic loads via experimental testing and numerical simulations. The re-entrant honeycomb design displayed the most consistent auxetic behaviour. Quasi-static compression and drop hammer impact tests were performed using the proposed full-scale sandwich panel design with two different configurations as a protective system for concrete wall structures in combination with plastic face plates. The effect of the internal angle of the re-entrant honeycomb design and the effect of the core material under static and dynamic loads were evaluated using full-scale sandwich panels. Furthermore, two separate materials – acrylonitrile butadiene styrene and low-density polyethylene – were used as face plates, and the low-density polyethylene was effective for lightweight and smooth load transferring and distribution into the auxetic core. Auxetic panel deformation under static and dynamic load was examined using a normal speed camera and high-speed video recording data and all auxetic panels indicated excellent systematic crushing behaviour with drawing materials into the load path to effectively resist the impact load. Numerical simulations were performed using LS-DYNA and indicated good agreement with the experimental results. Finally, protective systems utilising sandwich panels with a re-entrant honeycomb core indicated strong potential for the development of high-performance lightweight impact-resistant protective systems.